If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x = -36 Multiply x * x x2 = -36 Solving x2 = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x2 = -36 Reorder the terms: 36 + x2 = -36 + 36 Combine like terms: -36 + 36 = 0 36 + x2 = 0 The solution to this equation could not be determined.
| 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n | | 8(x+12)-288=3x | | 3q+4=2q+10 | | 2x^2+8x=192 | | 8x+35=6x+27 | | n^2+-3n+-40=0 | | 7x+1=52 | | 10v^2-21v-49=0 | | 2x^3+8x^2-64=0 | | n^2+2n+-24=0 |